Measurement of the absolute differential cross section for np elastic scattering at 194 MeV - M. Sarsour (2018)
A tagged medium-energy neutron beam was used in a precise measurement of the absolute differential cross section for np backscattering. The results resolve significant discrepancies within the np database concerning the angular dependence in this regime. The experiment has determined the absolute normalization with ±1.5% uncertainty, suitable to verify constraints of supposedly comparable precision that arise from the rest of the database in partial wave analyses. The analysis procedures, especially those associated with the evaluation of systematic errors in the experiment, are described in detail so that systematic uncertainties may be included in a reasonable way in subsequent partial wave analysis fits incorporating the present results. © 2006 The American Physical Society.